OC-010 Epigenome-wide dna methylation profiling in inflammatory bowel disease. (22nd June 2015) - Ventham, NT; Kennedy, NA; Adams, AT; Kalla, R; O'Leary, KR; Wilson, DC; Nimmo, ER; Satsangi, J
Abstract : Introduction: Epigenetic alterations including DNA methylation may provide important insights into gene-environment interaction in complex immune diseases such as inflammatory bowel disease (IBD). Whilst whole tissue methylation changes may provide clinically useful biomarkers, epigenetic changes are cell-type specific. This study aimed to characterise the circulating methylome in IBD, and relate changes seen in whole blood to the methylation profile in separated leucocytes, gene expression data, as well as our previous data in childhood-onset disease. 1 Method: The Illumina 450k array was used to assess whole blood leucocyte DNA methylation at over 485, 000 CpG sites across the genome in 240 patients (121 Crohn's disease [CD], 119 ulcerative colitis [UC]) and 191 controls. Differentially methylated sites discovered in whole blood were investigated in immunomagnetically separated leucocytes (CD4 + and CD8 + lymphocytes, CD14 + monocytes). Results: There were 439 differentially methylated positions (DMPs) meeting epigenome wide significance as defined as a Holm corrected p value of <0.05 (uncorrected p < 1.1 × 10 –7 ) in IBD cases versus control. No markers were significantly different between CD and UC. There were 55 differentially methylated regions (DMRs) with unidirectional methylation change in 3 or more adjacent markers each achieving False Discovery Rate significance of p < 0.05. Of these, 6 were significant following more stringent Holm correction. There was significant enrichment of methylation alteration around known susceptibility loci. 2 Linear Discriminant analysis using two CpG sites discriminated IBD cases and controls with high accuracy (area under curve 0.87). Established as well as novel pathways pertinent to disease pathogenesis are strongly implicated. The most significantly DMP in whole blood (RPS6KA2 [corrected p = 1.2 × 10 –16 ] was also hypomethylated in monocytes in UC (uncorrected p = 3.5 × 10 –6 ). The most significant DMR, VMP1/miR21 (most significant probe corrected p = 2 × 10 –14 ) strongly replicates the same finding in our previous study. The gene encoding Beta-2 Integrin (ITGB2) was a hypermethylated DMR in IBD and more specifically CD (most significant probe corrected p = 3.3 × 10 –5 ) compared with controls. Conclusion: This is the most detailed characterisation of the epigenome carried out in IBD to date and includes novel data exploring the circulating methylome in UC. The findings strongly validate this approach in complex disease, replicate and expand previous data, and provide clear translational opportunities. Disclosure of interest: N. Ventham Grant/Research Support from: EC grant IBD-BIOM, Conflict with: Abbvie, MSD speakers fees, N. Kennedy Grant/Research Support from: Wellcome Trust, Conflict with: Abbvie, MSD, Warner Chilcott, Ferring speakers fees. Shire Travel bursay, A. Adams: None Declared, R. Kalla: None Declared, K. O'Leary: None Declared, IBD BIOM consortium: None Declared, D. Wilson Grant/ Research Support from: MRC, CICRA, and EC grant IBD-BIOM, Consultant for: Pfizer, Conflict with: MSD investigator grant, MSD speaker fee, and Ferring speaker fee, E. Nimmo Grant/ Research Support from: EC grant IBD-BIOM, CSO, J. Satsangi Grant/ Research Support from: EC grant IBD-BIOM, Wellcome, CSO, MRC, Consultant for: Takeda, Conflict with: MSD speaker fees. SHire travelling expenses. References: Adams AT, et al . IBD 2014;20(10):1784–93 Jostins L, et al . Nature 2012; 491(7422):119–24